Respon Pemberian Karbon Aktif Arang Sekam terhadap Pelepasan Gas Amonia pada Feses Ayam Ras Petelur - Sara, U.; Azhar, M.; Aulyani, T. L.; Faradila, S. (Universitas Islam Negeri Alauddin Makassar, 2024)
This study aims to determine the response of activated carbon from rice husk charcoal to the release of ammonia gas in the manure of laying hens. This study used 12 laying hens of the Isa Brown strain aged 70 weeks. Manure collection is done in the morning. The manure of laying hens was collected as much as 50 grams for each treatment. The manure that has been collected is then sprinkled with activated carbon from husk charcoal. Manure that has been sprinkled with activated carbon is stored for 7 days at room temperature. The administration of activated carbon charcoal husk was divided into 4 treatments with 3 replications. The first treatment was 50 g of manure + without giving rice husk charcoal (Control), the second treatment was 50 g of manure + 10% activated carbon (rice husk charcoal), the third treatment was 50 g of manure + 20% activated carbon (rice husk charcoal), and the fourth treatment was 50 g manure + 30% activated carbon (rice husk charcoal). The results showed that the administration of activated carbon husk charcoal at different concentrations was able to increase the temperature and reduce the levels of ammonia, especially in the treatment of 10% activated carbon of husk charcoal), but had not been able to change the shrinkage and pH of manure. The recommended treatment is activated carbon charcoal husk treatment at a concentration of 10%.